Charge-specific adverse effects of polystyrene nanoplastics on zebrafish (Danio rerio) development and behavior. (May 2022) - Teng, Miaomiao; Zhao, Xiaoli; Wu, Fengchang; Wang, Chengju; Wang, Chen; White, Jason C.; Zhao, Wentian; Zhou, Lingfeng; Yan, Sen; Tian, Sinuo
Graphical abstract: Highlights: Differentially charged PS-NP accumulated in brain of zebrafish larvae. PS-NH2 induced more serious cell apoptosis in brain than PS-COOH. 13 altered metabolites related to NMDA2B in PS-NH2 exposure. 3 changed metabolites related to GPRs were increased by PS-COOH exposure. Stronger binding between NMDA2B with PS-NH2 than PS-COOH affected behaviors. Abstract: Nanoplastics are being detected with increasing frequency in aquatic environments. Although evidence suggests that nanoplastics can cause overt toxicity to biota across different trophic levels, but there is little understanding of how materials such as differently charged polystyrene nanoplastics (PS-NP) impact fish development and behavior. Following exposure to amino-modified (positive charge) PS-NP, fluorescence accumulation was observed in the zebrafish brain and gastrointestinal tract. Positively charged PS-NP induced stronger developmental toxicity (decreased spontaneous movement, heartbeat, hatching rate, and length) and cell apoptosis in the brain and induced greater neurobehavioral impairment as compared to carboxyl-modified (negative charge) PS-NP. These findings correlated well with fluorescence differences indicating PS-NP presence. Targeted neuro-metabolite analysis by UHPLC-MS/MS reveals that positively charged PS-NP decreased levels of glycine, cysteine, glutathione, and glutamic acid, while the increased levels of spermine, spermidine, and tyramine were induced by negatively charged PS-NP. Positively charged PS-NP interacted with the neurotransmitter receptor N-methyl-D-aspartate receptor 2B (NMDA2B), whereas negatively charged PS-NP impacted the G-protein-coupled receptor 1 (GPR1), each with different binding energies that led to behavioral differences. These findings reveal the charge-specific toxicity of nanoplastics to fish and provide new perspective for understanding PS-NP neurotoxicity that is needed to accurately assess potential environmental and health risks of these emerging contaminants.